Social Ties and Foreign Market Entry - Ellis, Paul (Journal of International Business Studies, 2000)
The social dynamics which precede international exchange are considered in light of data collected on 133 foreign market entries from a sample of highly-internationalized manufacturing firms. Consistent with research done in the social network field, the findings support the hypothesis that knowledge of foreign market opportunities is commonly acquired via existing inter-personal links rather than collected systematically via market research. This study thus contributes towards an understanding of those antecedent conditions that lead to the formation of export exchange relationships.